(untitled) (International journal of medical sciences, 2026)
Crush syndrome (CS), or traumatic rhabdomyolysis, is a life-threatening systemic condition caused by prolonged compression of skeletal muscle. It remains a major contributor to morbidity and mortality in mass disasters such as earthquakes and building collapses. This literature review summarizes recent evidence on the epidemiology, mechanisms of onset, and sequential pathophysiological processes of CS. Epidemiological data indicate that CS accounts for 2–5% of earthquake-related injuries, with mortality rates reaching 40% in severe cases. The pathogenesis involves sustained ischemia, reperfusion injury, and subsequent rhabdomyolysis, leading to massive release of intracellular contents including myoglobin and potassium. These changes cause life-threatening electrolyte disturbances, acute kidney injury, and systemic inflammatory responses that progress to multi-organ dysfunction. Early diagnosis and prompt interventions—such as fluid resuscitation, electrolyte correction, and renal support—are essential to improving outcomes. Understanding the underlying pathophysiological processes provides critical insights for disaster medicine, emergency care, and future therapeutic strategies.